Levin C. Handy papers - Handy, Levin C. (Levin Corbin), 1855-1932.
Letters to Handy chiefly regarding requests for photographs or services from his photography business in Washington, D.C. Includes correspondence of his uncle, Mathew B. Brady.
Photographer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brady, Mathew B., -- approximately 1823-1896 -- Correspondence; Photography -- Washington (D.C.); Photographers